Recent advances in narcolepsy - Paul Reading (Advances in Clinical Neuroscience & Rehabilitation, 2016)
Narcolepsy is thought to affect 0.05% of Caucasian populations and frequently causes severe symptoms across the 24-hour period. It is best viewed as a disorder of sleep-wake regulation with particular abnormalities of the rapid eye movement (REM). Typical cases are due to specific loss of a subset of hypothalamic neurons containing the neuropeptide, hypocretin (orexin). Several lines of evidence, including a causal link to the swine ‘flu vaccination, suggest autoimmune destruction of these neurons as an initial event.